Do gender and science success moderate the effects of science learning self-efficacy on science identity? - Belova, Tatyana; Islamov, Artem E.; Rozhnov, Artemiy A.; Zhdanov, Sergei P.; Sokolova, Ekaterina I.; Tsomartova, Dibakhan A. (Frontiers in Education, 2024)
Introduction This study investigates the relationship between science learning self-efficacy and science identity, examining how gender and science success moderate this relationship. Methods Using a quantitative approach with Partial Least Squares Structural Equation Modeling, data from high school students in Moscow, Almetyevsk, Khabarovsk cities from Russia were analyzed. Results The research highlights the significant positive impact of integrative science competence, practical science application, and science communication efficacy on science identity. Interestingly, gender did not significantly influence the efficacy-identity relationship, suggesting its minimal role in this context. Conversely, science success, particularly in conjunction with science communication efficacy, played a notable role, indicating a complex interplay that could affect students’ science identity. Discussion These findings emphasize the need for educational strategies that bolster students’ self-efficacy in science, catering to the development of a strong science identity. Future research should explore the nuanced effects of success and communication efficacy on science identity, aiming to inform interventions that support diverse and equitable participation in science education and careers.